Α‐2‐macroglobulin, an infection‐resistant biomarker in Epinephelus fuscoguttatus (Forsskål, 1775). (15th August 2022) - Ibrahim, Nur Liyana; Webb, Conner; Nazarudin, Muhammad Farhan; Min, Chong Chou; Din, Mohamed Shariff Mohamed; Robinson, Colin; Abdullah, Maha
Abstract: Epinephelus fuscoguttatus (Forsskål), or brown‐marbled grouper, is a favoured species among aquaculture farmers for its relative easy management and high commercial value. Disease outbreaks, however, negatively impact farmers' livelihoods by reducing fish harvest yields. Traditional selective breeding of disease‐resistant strains is still being practised due to limitations in vaccines and effective antibiotics. Development of biomarkers and molecular quantitative techniques has potential to advance approaches in handling outbreaks of disease. This study aimed to determine selected proteins' expression patterns and suitability as infection‐resistant markers in brown‐marbled grouper. Experimental infection of brown‐marbled grouper with Vibrio parahaemolyticus was established. Fingerlings ( N  = 70) were acclimatized and maintained in saltwater at 28 ± 2°C, pH 7.9 ± 1, salinity 29 ± 1 ppt and dissolved oxygen 5 ppm. V. parahaemolyticus at 5 × 10 11 CFU/ml was injected into the dorsal area of the fish and monitored for 7 days. Expressions of alpha‐2‐macroglobulin, nattectin and parvalbumin were determined in liver, spleen, and blood cells by quantitative PCR. Alpha‐2‐macroglobulin in plasma was detected by western blot immunoassay. Clinical signs of infection included skin haemorrhagic lesions and depigmentation. Susceptible and resistant fish were differentiated by lesions >5 cm and absence of lesion at injection site, respectively. Infection significantly increased expression of alpha‐2‐macroglobulin, nattectin and parvalbumin in the liver and spleen but not in blood cell samples. Levels of alpha‐2‐macroglobulin and parvalbumin were significantly increased in liver of susceptible grouper, whereas alpha‐2‐macroglobulin significantly increased in plasma of resistant fish. In conclusion, alpha‐2‐macroglobulin is a potential infection‐resistant biomarker in brown‐marbled grouper and readily detected in fish plasma.